2003
DOI: 10.1103/physrevlett.91.033201
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion Energy from Density-Functional Theory Description of Monomers

Abstract: A method is proposed for calculations of dispersion energy at finite intermonomer separations. It uses a generalized Casimir-Polder formula evaluated with dynamic density susceptibilities provided by time-dependent density-functional theory. The method recovers the dispersion energies of He, Ne, and H2O dimers to within 3% or better. Since the computational effort of the new algorithm scales approximately as the third power of system size, the method is much more efficient than standard wave-function methods c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
425
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 360 publications
(431 citation statements)
references
References 34 publications
4
425
2
Order By: Relevance
“…38 The ab initio method used was SAPT(DFT): symmetry-adapted perturbation theory (SAPT) based on monomer wave functions, orbital energies, and response properties obtained from (time-dependent) DFT calculations. This method, initially proposed by Williams and Chabalowski, 63 was later extended and implemented by Misquitta et al [64][65][66] and by Heßelmann et al 37,67,68 It is much more economical than the regular SAPT 69 or the coupledcluster method using single, double, and perturbative triple excitations, CCSD(T), the two approaches that have established themselves currently as the most accurate of practically applicable methods for obtaining intermolecular interaction potentials. Both groups have shown that SAPT(DFT) results for the benzene dimer are about as accurate as the results from CCSD(T).…”
Section: Introductionmentioning
confidence: 99%
“…38 The ab initio method used was SAPT(DFT): symmetry-adapted perturbation theory (SAPT) based on monomer wave functions, orbital energies, and response properties obtained from (time-dependent) DFT calculations. This method, initially proposed by Williams and Chabalowski, 63 was later extended and implemented by Misquitta et al [64][65][66] and by Heßelmann et al 37,67,68 It is much more economical than the regular SAPT 69 or the coupledcluster method using single, double, and perturbative triple excitations, CCSD(T), the two approaches that have established themselves currently as the most accurate of practically applicable methods for obtaining intermolecular interaction potentials. Both groups have shown that SAPT(DFT) results for the benzene dimer are about as accurate as the results from CCSD(T).…”
Section: Introductionmentioning
confidence: 99%
“…These calculations were performed using the DALTON 2.0 program. 36 For deeper insight into the nature of the interaction energies we have additionally used the CamCASP program 37 to perform symmetry adapted perturbation theory (SAPT) DFT [38][39][40] calculations to decompose the interaction energies into physical components. Fig.…”
Section: Beyond the Pbe Functional A Calculations For Molecularmentioning
confidence: 99%
“…Ref. 31 for an equivalent route to DFT-SAPT dispersion energies͒ which were also used to determine its exchange correction. The PBE0AC xc-potential, introduced and defined in Ref.…”
Section: A Dft-sapt Calculationsmentioning
confidence: 99%